Pendekatan kognitif dalam penilaian prestasi - Foo,, Peter Chee Hui (1997)
This study aims to determine how far do the purpose of observation and the time lapse between time of observation and time of rating influence the quality of performance appraisal rating of teachers by secondary school principals.